Challenges Hindering the Utilization of Social Innovation Programs: A Study of the Reality of Social Work Pioneers - A descriptive study of enrollees in social innovation programs at Princess Al-Anoud Foundation, Riyadh, Kingdom of Saudi Arabia - May 2025 - Almansouri, Maryam Saeed; Al-Bunyan, Asma Mohammed (Journal of Humanities & Social Sciences, 2025)
This study aimed to identify the challenges that hinder the effective utilization of social innovation programs by social entrepreneurs at the Princess Al-Anoud Foundation in Riyadh. A descriptive survey method was adopted using a comprehensive enumeration approach, with an electronic questionnaire distributed to 178 participants, of which 142 valid responses were collected, achieving a response rate of 79.8%. The findings revealed that the overall mean score of challenges was (3.68 out of 5), indicating a high level of agreement. The most prominent challenges were the lack of specialized innovation centers (mean = 3.97), limited organizational attention to social innovation (3.91), insufficient financial support (3.89), weak incentives for innovation products (3.87), and limited integration of artificial intelligence tools (3.81). Cultural and psychological barriers were also evident, such as limited awareness of social innovation (3.69) and fear of failure (3.44). The study concludes that institutional, technical, cultural, and psychological challenges collectively reduce the effectiveness of social innovation programs, and it recommends establishing innovation hubs, providing financial and advisory support, and integrating modern technologies to enhance their societal impact.
Keywords: Social Innovation; Challenges; Social Work Pioneers; Social Entrepreneurship; Creative Thinking; Problem Solving